Proceedings of 2013 World Agricultural Outlook Conference - Xu, Shiwei.; Xu, Shiwei. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Food security has always been a major global concern and is getting more attention in recent years. In fact, the global economy and stability has been severely challenged by the precarious state of food security, which was exacerbated by a combination of sharp price volatility and disastrous weather conditions related to climate change. The book aims to improve the analysis and projection of agricultural production and marketing, facilitates information exchange to better food supply and demand, and ultimately contributes to enhance world food security and sustainable global agricultural development.